2013
DOI: 10.1177/1470357213483059
|View full text |Cite
|
Sign up to set email alerts
|

The melodrama of being a child: NGO representations of poverty

Abstract: This article shows how NGO films deploy melodramatic modes in constructing the narrative arcs of their campaign films and it explores the potential of this mode for generating solidarity between the spectator and the suffering subject. The author analyses how, through the use of music, colour and gesture, a visceral emotional response is evoked that produces an identification of the spectator with the experiences of the suffering subject. She argues that the criticism of melodrama as a mode or genre that subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…It is interesting – although perhaps not surprising given previous literature – that the videos embodied more attributes framed by pathos appeals. This is in line with existing research that suggests video's general penchant to communicate emotional qualities (Stiles ; Wells ) and supports assertions regarding the importance of ethos (English et al . ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is interesting – although perhaps not surprising given previous literature – that the videos embodied more attributes framed by pathos appeals. This is in line with existing research that suggests video's general penchant to communicate emotional qualities (Stiles ; Wells ) and supports assertions regarding the importance of ethos (English et al . ).…”
Section: Discussionsupporting
confidence: 91%
“…However, fundraising videos and public service adverts are largely characterised by pathos appeals. Economist Karen Wells () suggested that such videos could evoke feelings of solidarity via visceral responses to music, colour and gesture. Similarly, Stile's (, 201) ‘best practices’ for public service announcements can be described by emotive tactics such as authenticity, depicting the protagonist's ‘depth of character’, and with an audience‐focused selection of narrative and imagery.…”
Section: Fundraising and Public Service Videosmentioning
confidence: 99%
“…This rhetoric was targeted above all at ending widespread child labor in mines, sweatshops, mills, and factories (Wells, 2008(Wells, , 2013, as well as forming a part of the 'civilizing mission' towards peoples in far-flung colonies that many nineteenth-century Europeans regarded as their providential destiny. By the mid-twentieth century, however, that rhetoric had largely been superseded by a rights-based discourse that focused on the 'best interests of the child,' as a basis for legal reforms and policies of Western governments and NGOs (Wells, 2013). The key manifestation of this shift may have been the 1959 United Nations Declaration of the Rights of the Child, the first legally binding international instrument to incorporate civil, political, economic, social, and cultural rights: the right to survival; to develop to the fullest; to protection from harmful influences, abuse, and exploitation; and to participate fully in family, cultural, and social life.…”
Section: Sponsoring Saving Parentingmentioning
confidence: 99%
“…It also reveals a broad adherence to the idea that sponsoring promotes economic development and market principles that foster general ‘thriving.’ Both the name of the organization and the text of the caption, however, turn the action of sponsoring into an act of ‘saving.’ In so doing, the NGO embeds donors’ acts of charity in a rhetoric of child saving that goes back to the nineteenth century and early twentieth century in the Anglo-American world and continental Europe. This rhetoric was targeted above all at ending widespread child labor in mines, sweatshops, mills, and factories (Wells, 2008, 2013), as well as forming a part of the ‘civilizing mission’ towards peoples in far-flung colonies that many nineteenth-century Europeans regarded as their providential destiny. By the mid-twentieth century, however, that rhetoric had largely been superseded by a rights-based discourse that focused on the ‘best interests of the child,’ as a basis for legal reforms and policies of Western governments and NGOs (Wells, 2013).…”
Section: Sponsoring Saving Parentingmentioning
confidence: 99%
“…Tal y como los trabajos precursores de Reguillo y Colón indagaron -a comienzos del siglo XXI-sobre el despliegue discursivo melodramático, más allá de los formatos de la ficción televisiva, hoy encontramos signos alentadores en ese mismo sentido. Trabajos de investigación provenientes de otras áreas de las humanidades y de las ciencias sociales están identificando cómo el modo melodramático está también estructurando discursos noticiosos e incluso discursos de organizaciones de la sociedad civil y la política parlamentaria (Anker, 2014;Griffiths, 2018;Mujica & Bachmann;Wells, 2013).…”
unclassified